2018
DOI: 10.1002/solr.201800122
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Ionization Potential and Oxidation Potential of Organic Semiconductor Films Used in Photovoltaics

Abstract: Ultraviolet photoelectron spectroscopy (UPS) and cyclic voltammetry (CV) are employed to measure energy levels for charge transport in organic semiconductor films. A series of classical molecules/polymers used in organic bulk heterojunction solar cells are deposited on platinum substrates/ electrodes to form thin films and a linear relationship of vertical ionization potential (IP) measured by UPS and relative oxidation potential (E ox ) obtained by CV is found, with a slope equal to unity. The intercept varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…In this case, Deming regression gives a slope of 1.07 ( Figure 8). [40] The spread in the data around the best-fit line in Figure 8 can be partially attributed to the experimental uncertainty of the data points: about ±0.05 eV for E HOMO,SWV and about ±0.10 eV or in some cases slightly more for E HOMO,UPS . Energy Mater.…”
Section: Correlation Between the Homo Energy From Swv Ups And Dftmentioning
confidence: 95%
See 3 more Smart Citations
“…In this case, Deming regression gives a slope of 1.07 ( Figure 8). [40] The spread in the data around the best-fit line in Figure 8 can be partially attributed to the experimental uncertainty of the data points: about ±0.05 eV for E HOMO,SWV and about ±0.10 eV or in some cases slightly more for E HOMO,UPS . Energy Mater.…”
Section: Correlation Between the Homo Energy From Swv Ups And Dftmentioning
confidence: 95%
“…Fc/Fc + is one of the redox couples recommended by the International Union of Pure and Applied Chemistry for reporting energy levels in nonaqueous solvents. [36][37][38][39][40] This would alter the proportionality constant between E CT and (E HOMO,D − E LUMO,A ). [35] Recently, several experimental studies of the oxidation potential as obtained from CV (E ox,CV ) and ionization potential from UPS (IP) have revealed that both quantities are linearly correlated, i.e., IP = α + qE ox,CV + β + , but that the best-fit slope varies considerably from α + = 0.9 to 1.5, depending on the material class.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2c), evidencing the relatively weaker electron-donating nature of the IDT unit. 37,38 With theoretical understanding of the structural features of axisymmetric CDT vs. centrosymmetric IDT Figures S10-13). Four regioregular polymers with the FBT units facing the same regular pattern along the backbones yet different backbone compositions were synthesized from the corresponding monomers under the same conditions (Ph(PPh 3 ) 4 as the catalyst in o-xylene under microwave heating at 220°C), as shown in Scheme 1.…”
Section: Synthesis Characterization and Computational Analysismentioning
confidence: 99%